A New Classification of Three-Dimensional Printing Technologies: Systematic Review of Three-Dimensional Printing for Patient-Specific Craniomaxillofacial Surgery. Issue 5 (May 2017) - Jacobs, Carly A.; Lin, Alexander Y.
Abstract : Background: Three-dimensional printing technology has been advancing in surgical applications. This systematic review examines its patient-specific applications in craniomaxillofacial surgery. Methods: Terms related to "three-dimensional printing" and "surgery" were searched on PubMed on May 4, 2015; 313 unique articles were returned. Inclusion and exclusion criteria concentrated on patient-specific surgical applications, yielding 141 full-text articles, of which 33 craniomaxillofacial articles were analyzed. Results: Thirty-three articles included 315 patients who underwent three-dimensional printing–assisted operations. The most common modeling software was Mimics, the most common printing software was 3D Systems, the average time to create a printed object was 18.9 hours (range, 1.5 to 96 hours), and the average cost of a printed object was $1353.31 (range, $69.75 to $5500). Surgical procedures were divided among 203 craniofacial patients (205 three-dimensional printing objects) and 112 maxillofacial patients (137 objects). Printing technologies could be classified as contour models, guides, splints, and implants. For craniofacial patients, 173 contour models (84 percent), 13 guides (6 percent), two splints (1 percent), and 17 implants (8 percent) were made. For maxillofacial patients, 41 contour models (30 percent), 48 guides (35 percent), 40 splints (29 percent), and eight implants (6 percent) were made. These distributions were significantly different ( p < 0.0001). Four studies compared three-dimensional printing techniques to conventional techniques; two of them found that three-dimensional printing produced improved outcomes. Conclusions: Three-dimensional printing technology in craniomaxillofacial surgery can be classified into contour models (type I), guides (type II), splints (type III), and implants (type IV). These four methods vary in their use between craniofacial and maxillofacial surgery, reflecting their different goals. This understanding may help advance and predict three-dimensional printing applications for other types of plastic surgery and beyond. Abstract : Supplemental Digital Content is available in the text.